PERLINDUNGAN HUKUM TERHADAP INFLUENCER ATAS KORBAN TINDAK PIDANA CYBERBULLYING PADA MEDIA SOSIAL INSTAGRAM - Herlina Aprilia; Abu Hapsin; Nazar Nurdin (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2023)
The influence of the development of technology and information in Indonesia has become a double-edged sword. On the one hand, it provides welfare and benefits to the people who use it; on the other hand, at the same time, it also creates crime. Crime in the field of technology that often occurs is cyberbullying, a term used based on bullying behaviour in cyberspace. The research aims to analyse legal protection for cyberbullying victims by netizens towards Instagram influencers. This research was conducted using the normative-empirical method, namely the implementation of normative legal provisions and legal events in society. The study results show that, first, legal protection for victims of cyberbullying has been included in statutory regulations. Second, legal protection can be obtained through institutions, and there are prevention efforts as a form of victim protection. Therefore, conceptually, legal protection for victims can be done through various means, such as by implementing laws and institutions